2022
DOI: 10.3389/fruro.2022.1017069
|View full text |Cite
|
Sign up to set email alerts
|

Thulium fiber laser in BPH surgery: Bench to bedside - a systematic review on behalf of YAU Urotechnology Working Group

Abstract: IntroductionThe Thulium fiber laser (TFL) is a new device that in contrast to the other solid-state YAG-based lasers takes a different approach to pulse formation allowing for two different modes: in the QCW (quasi-continuous wave) function, TFL is convenient for soft tissue surgery and in the SP (Superpulsed) mode it is highly effective in lithotripsy. Thus, unlike the other thulium lasers (Tm : YAG), TFL can be used in a wide range of surgical procedures.Materials and MethodsWe conducted a systematic search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…However, our study showed no significant differences regarding overall operation time and morcellation time. This finding is supported by all previous data and the review of Taratkin et al [ 10 , 18 , 19 , 22 ]. Although the TFL was a relatively new laser source for our surgeons, who were all used to the holmium laser, our reported ThuFLEP enucleation efficiency of 1.45g/min is still higher than achieved in other publications (1.04 to 1.40g/min) [ 8 , 10 , 13 , 17 , 19 , 20 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, our study showed no significant differences regarding overall operation time and morcellation time. This finding is supported by all previous data and the review of Taratkin et al [ 10 , 18 , 19 , 22 ]. Although the TFL was a relatively new laser source for our surgeons, who were all used to the holmium laser, our reported ThuFLEP enucleation efficiency of 1.45g/min is still higher than achieved in other publications (1.04 to 1.40g/min) [ 8 , 10 , 13 , 17 , 19 , 20 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…The only randomized prospective study, which was conducted by Enikeev et al defined the severity of urinary incontinence according to the ICIQ-MLUTS as primary outcome [ 10 ]. There is still limited evidence on the use and clinical outcomes of ThuFLEP [ 8 , 21 , 22 ]. To fill this void, we conducted the following prospective randomized trial.…”
Section: Introductionmentioning
confidence: 99%
“…During prostate enucleation, extensive energy consumption could lead to tissue carbonization “black escharing” which might obscure the surgical planes and cause harm to the adjacent capsule and urethral sphincter [ 16 ]. Therefore, mechanical dissection-dependent enucleation using different lasers has been advocated by some authors to avoid loss of surgical planes, whereas the prostate enucleation relies mainly on the mechanical dissection exerted through the resectoscope sheath tip after making the initial incisions [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%